Hatchu (Herbal Touch for Your Foot): Natural Foot Spray Formulated from Citrus Peel Waste and Local Plant Ingredients to Prevent Foot Odor - Jasmeen Nur Rahmania; Aisya Nayla Savitri; Noya Karaisha Madina Setiawan; Nunis Nurmaulida; Jahida Ilmi Lutfia Nugraha; Rosi Ari Ramdani (Journal Educational Research and Development | E-ISSN : 3063-9158, 2026)
Foot odor is a common issue that can affect personal comfort and self-confidence, particularly among individuals who engage in daily activities while wearing closed footwear for extended periods. This condition is generally associated with excessive moisture and poor ventilation of the feet. To address this problem, this study aimed to develop HATCHU Foot Spray, a natural foot spray formulated as a hygienic and environmentally friendly product. The research was conducted as a school-based project focusing on product formulation and user acceptance. The spray was formulated using orange peel waste and betel leaf extracts, selected based on information from previous studies regarding their potential properties when used in personal hygiene products. The formulation process emphasized simple preparation methods suitable for student-level research. Product evaluation focused on observable characteristics and user perception, including aroma, ease of use, and overall comfort after application. The results indicated that the foot spray had a fresh natural scent and was positively received by users. Most respondents reported a pleasant sensation and improved comfort after use, which contributed to good overall acceptance of the product. This study demonstrates that HATCHU Foot Spray can be successfully formulated as a natural foot hygiene product using locally available materials and waste resources. However, this research did not include laboratory-based antibacterial testing or clinical evaluation. Therefore, the findings are limited to formulation outcomes and user perceptions. Further studies involving controlled laboratory testing are recommended to evaluate the functional properties of the product in greater detail.